An unusual presentation of a rare neoplasm - Waldenstrom’s macroglobulinemia - A. Samartha, Vinitha; Hegde, Shreya; R Pai, Muktha; Ahmed, Zulfikar (Tropical Journal of Pathology and Microbiology, 2019)
Waldenstrom’s macroglobulinemia (WM) is a rare malignant lymphoproliferative disorder with an overall incidence of 2.5cases/ million/year. This is a case report of a 48-year-old woman who presented with an unusual, yet significant gastrointestinal involvement. Biopsy of the duodenum clinched the diagnosis of WM. Further bone marrow and serum electrophoresis confirmed the diagnosis. WM is an uncommon slow growing malignant monoclonal gammopathy which is chronic, indolent and predominantly involving the bone marrow and characterized by secretion of high levels of monoclonal immunoglobulin (IgM–hence called macroglobulinaemia), elevated serum viscosity and presence of lymphoplasmacytic infiltration of the bone marrow. This causes the most common non specific symptom of weakness and easy fatiguability. In some individuals, the IgM proteins clump together in the hands and feet, where the body temperature is cooler than at the centre of the body, hence being referred to as cryoglogubulins, their clumping causing a condition called cryoglobulinemia. Extramedullary involvement is rare and may affect central nervous system, articular and periarticular structures, lungs, kidneys, eyes, and gastrointestinal system.